Developing a professional identity in a new work environment: the views of defendant intermediaries working in the criminal courts. Issue 2 (9th May 2016) - O'Mahony, Brendan M.; Creaton, Jane; Smith, Kevin; Milne, Rebecca
Abstract : Purpose: – The purpose of this paper is to find out how intermediaries interpret their role working with vulnerable defendants at court. Design/methodology/approach: – In this study six intermediaries who have worked with defendants were interviewed using a semi-structured interview and the interview transcripts were analysed using interpretative phenomenological analysis. Findings: – Intermediaries appeared to be trying to make sense of their developing identities as professionals in the courtroom and this theme is conceptualised through social identity complexity theory. Practical implications: – Health and care professionals undertaking a new function in the criminal justice sector should receive training about the psychological processes underlying developing professional identities. Such training should reduce the cognitive load when they work in the new environment and failure to undertake this training may lead to less efficient practice. Gaining an understanding of their professional positioning within the court environment may assist with retention of intermediaries in this new role. Originality/value: – This is the first published study where intermediaries have been interviewed about their experiences with defendants. Recommendations are made including the requirement for additional training for intermediaries to understand the underlying psychological processes and conflicts they may experience when working with defendant cases.